On not dying : secular immortality in the age of technoscience - Farman, Abou, 1966- (University of Minnesota Press, 2020)
"Farman's Secular Immortal examines "immortalists," people who believe that it is possible for humans to achieve immortality through technoscientific means. These "immmortalists" include people who choose to have their bodies and/or brains frozen in the hopes that they can be reanimated, but also scientists and biologists engaged with extending the natural life of the human. Part history, part philosophical anthropology, and part ethnography, the work is based on communities of immortalists and advocates as well as institutions and organizations engaged in the definition of the end of life, including funeral homes, insurance companies, and lawyers. By looking at three such 'immortalist' strategies (cryonics, biogerontology, and artificial intelligence), Farman's study explores the cultural logic through which immortality projects move betwixt and between logics of religion, secularism, and philosophy"--